2016
DOI: 10.1016/j.ibiod.2016.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Biological performance and trace organic contaminant removal by a side-stream ceramic nanofiltration membrane bioreactor

Abstract: This study evaluated the performance of a side-stream ceramic nanofiltration membrane bioreactor (NF-MBR) system with respect to basic water quality parameters as well as trace organic contaminant (TrOC) removal efficiency. The results show a stable biological performance of the continuous NF-MBR system with high effluent quality (total organic carbon < 4 mg L-1 and NH4 +-N below the detection limit). Significantly higher performance by this NF-MBR in comparison to the conventional microfiltration/ultrafiltrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…In addition to the use of high retention membranes that allows effective retention of pollutants including TrOCs, HR-MBRs may have different features compared to the conventional MBR configuration (Figure 1a Figure 1c) and nanofiltration (NF)-MBR ( Figure 1d) have been investigated to-date (Luo et al 2017b, Phan et al 2016b, Wijekoon et al 2014b).…”
Section: Hr-mbr Configurationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the use of high retention membranes that allows effective retention of pollutants including TrOCs, HR-MBRs may have different features compared to the conventional MBR configuration (Figure 1a Figure 1c) and nanofiltration (NF)-MBR ( Figure 1d) have been investigated to-date (Luo et al 2017b, Phan et al 2016b, Wijekoon et al 2014b).…”
Section: Hr-mbr Configurationsmentioning
confidence: 99%
“…As mentioned before, three configurations of HR-MBR, namely membrane distillation bioreactor (MDBR), forward osmosis (FO-MBR) and nanofiltration (NF-MBR) have been investigated to-date (Fernandez-Fontaina et al 2012, Luo et al 2017b, Phan et al 2016b, Wijekoon et al 2014b. Depending on the physicochemical properties of TrOCs and the type of HR-MBR configuration, removal of TrOCs by HR-MBRs can range between 90-99% (Table 2).…”
Section: Aqueous Phase Removal Of Trocs By Hr-mbrmentioning
confidence: 99%
See 2 more Smart Citations
“…. Most studies of aerobic treatment demonstrated a good biotransformation of these seven biodegradable TrOCs, except for some variation in the case of trimethoprim and sulfamethoxazole(Luo et al, 2014;Phan et al, 2016;Wijekoon et al, 2013). Compared to aerobic treatment, it is speculated that the negative redox potential can enhance the biodegradation of sulfamethoxazole and trimethoprim(Alvarino et al, 2014;Narumiya et al, 2013;Yang et al, 2017) Xue et al (2010).…”
mentioning
confidence: 99%